Statistical modelling of extreme rainfall, return periods and associated hazards in the Bamenda Mountain, NW Cameroon - Afungang,Roland (2016)
The Bamenda mountain region has one of the highest frequencies of landslides in Cameroon and the lowlands are prone to floods. The occurrence of these hazards is attributed to the estimated 2500 mm of rainfall that the area receives annually. The aim of this paper was to estimate the maximum rainfall the area is likely to receive in future and to examine some past extreme rainfall episodes that triggered landslides and floods and their return periods. The type I extreme value (Gumble) distribution was used to make these estimates through an Excel worksheet. From the model, it was predicted that the area could receive a maximum rainfall of about 87.7mm/day in 3 years, 116.97mm/day in 25 years, 126.13mm/day in 50 years and 135.23/day in 100 year. Seven extreme rainfall episodes were identified within the 43 year study period with rainfall amounts ranging from 99.5mm/day to 129.3mm/day. The extreme rainfall episodes initiated both landslide and floods and with return periods ranging between 7.3 years to 68.9 years. Predicting these extreme cases can be useful in the construction of dams and bridges and further research on rainfall thresholds for rainfall-induced hazards affecting the region.